Postnatal development of the endocrine pancreas in mice lacking functional GABAB receptors - Crivello, Martin (2013)
Adult mice lacking functional GABAB receptors (GABAB1KO) have glucose metabolism alterations. Since GABAB receptors (GABABRs) are expressed in progenitor cells, we evaluated islet development in GABAB1KO mice. Postnatal day 4 (PND4) and adult, male and female, GABAB1KO, and wild-type littermates (WT) were weighed and euthanized, and serum insulin and glucagon was measured. Pancreatic glucagon and insulin content were assessed, and pancreas insulin, glucagon, PCNA, and GAD65/67 were determined by immunohistochemistry. RNA from PND4 pancreata and adult isolated islets was obtained, and Ins1, Ins2, Gcg, Sst, Ppy, Nes, Pdx1, and Gad1 transcription levels were determined by quantitative PCR. The main results were as follows: 1) insulin content was increased in PND4 GABAB1KO females and in both sexes in adult GABAB1KOs; 2) GABAB1KO females had more clusters (<500 μm(2)) and less islets than WT females; 3) cluster proliferation was decreased at PND4 and increased in adult GABAB1KO mice; 4) increased β-area at the expense of the α-cell area was present in GABAB1KO islets; 5) Ins2, Sst, and Ppy transcription were decreased in PND4 GABAB1KO pancreata, adult GABAB1KO female islets showed increased Ins1, Ins2, and Sst expression, Pdx1 was increased in male and female GABAB1KO islets; and 6) GAD65/67 was increased in adult GABAB1KO pancreata. We demonstrate that several islet parameters are altered in GABAB1KO mice, further pinpointing the importance of GABABRs in islet physiology. Some changes persist from neonatal ages to adulthood (e.g., insulin content in GABAB1KO females), whereas other features are differentially regulated according to age (e.g., Ins2 was reduced in PND4, whereas it was upregulated in adult GABAB1KO females).